Efeito do escore do trato reprodutivo na dinâmica folicular e dopplerfluxometria útero-ovariana em novilhas nelore (Bos indicus) - FRANÇA, Itamara Gomes de (2016)
The objective of this study was to evaluate the effect of the reproductive tract scoring (RTS) on follicular dynamics and utero-ovarian doppleflowmetry in Bos indicus heifers of nelore. Were used 34 females cattle the females were classified into three categories, according to RTS: RTS 1 (diameter of the uterine horns <15 mm and diameter of follicles <8 mm; RTS 2 (diameter of the uterine horns ≥ 15mm and follicles ≥8 mm; RTS3 (diameter of the uterine horns ≥15mm and presence of CL). Then, were synchronized with progestin/estradiol-based protocol, plus prostaglandin, for padronization of the follicular and luteal status. The monitoring of the follicular dynamics and utero-ovarian flowmetry was performed by B-mode, color doppler and spectral doppler ultrasonography during three times: Day 0 (D0; ear implant insertion); Day 10 (D10, detection preovulatory follicles) and; Day 18 (D18; determination of ovulation by detection of corpora lutea). The uterine diameter showed a significant increase between D0 and D10 in both categories. The ovulation rate was higher in the RTS 3 (P<0.05). There was no effect of RTS nor of examination day on vascularity and number of pixels of the the ovary (P>0.05). In the follicular dominance phase (D10), the higher vascularization occurred in RTS2, followed by RTS 1 and 3, respectively (P<0.05). The uterine PI and RI were not affected by RTS nor by the examination day (P>0.05). However, when these same rates were evaluated in the ovary, the RI showed significant effect of RTS and RTS x day (P=0.02). Progesterone concentrations at the beginning of trial (D0) were higher in the RTS 3 (P<0.05) and estradiol did not differ significantly between categories (P<0.05) at day of follicular dominance (D10). It was concluded that RTS influences the follicular growth, ovulation rate and vascularization of the uterine horns.